Media Relations 2.0 - Mutia Dewi (Jurnal Komunikasi, 2012)
Delivering media relations activities is a need for organizations to convey public the information they have released. Rapid increase of technology and public’s dynamic force Public Relations practitioners to be able to adapt on it. In the era of interactive communication, media relations activities can be done by applying communication technology through internet, therefore it can be performed effectively.